Analysis of Physical Fitness and Physical Activity Results of Female Undergraduate and Graduate Students - Aleksander Yurevich Osipov; Roman Sergeevich Nagovitsyn; Olga Igorevna Vaganova; Maxim Mikhaylovich Kutepov; Elena Alexandrovna Chelnokova; Tatyana Igorevna Ratmanskaya; Anna Vladimirovna Vapaeva (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2021)
Information about the volume and intensity of the physical activity of students is collected through various methods of inquiry. Questionnaire data needs to be compared with objective criteria of the physical fitness of students. The purpose of the present research is a comparison of the International Physical Activity Questionnaire (IPAQ) data and the results of functional fitness assessment tests of female undergraduate (n=639) and graduate (n=625) students. The IPAQ data were used to determine the level of physical activity in females. Data regarding the BMI and self-perceived physical fitness of females are collected. The physical fitness level of the female students was assessed using functional fitness assessment tests. The IPAQ results show significant (p<0.05) differences in the total weekly volume of physical activity of females. More weekly physical activity volume was found in female graduate students. The advantage in IPAQ results is achieved by significantly (p<0.01) more weekly physical activity in the office job. The weekly volume of health and sports physical activity is significantly (p<0.01) higher in female undergraduate students. The data on the volume of regular daily movement in female groups do not differ significantly. The results of fitness testing showed an insufficient level of physical fitness of female students of both groups. BMI results of female students are normal. A significant lack of the total volume of physical activity of students of both groups in comparison with the IPAQ data of female students of some European countries was revealed. Increasing the total amount of physical activity and improving the quality of physical activity is recommended.